Treatment of pistachio processing industry wastewaters by supercritical water oxidation in a continuous-flow reactor - Akgun, Mesut; Kipcak, Ekin (TAYLOR & FRANCIS LTD, 2025)
The objective of the present study is the treatment of pistachio processing industry wastewaters (PPIW) using the supercritical water oxidation method. The experiments were conducted within a 400-600 degrees C temperature range and a 30-150 s reaction time range, while maintaining a constant pressure of 25 MPa and using an O-2/COD ratio of 1:1. To observe the effects of the initial PPIW and O-2 concentrations on the treatment efficiency, experiments were also conducted with O-2/COD ratios ranging from 0.5 to 3, while maintaining a constant reaction temperature and time of 500degree celsius and 60 s, respectively. The influence of reaction temperature, reaction time and O-2/COD ratio on the total organic carbon (TOC) and total nitrogen (TN) contents of the liquid PPIW effluents were investigated. Treatment efficiencies up to 99.75% regarding TOC conversion and 78.72% regarding TN conversion were obtained in very short reaction times. Additionally, the kinetics of oxidation of PPIW was studied, and reaction rate expressions based on TOC and TN were proposed. [GRAPHICS] .
Keywords: Pistachio processing; wastewater; treatment; supercritical water oxidation; kinetics; WASTE-WATER; ELECTROCOAGULATION; ELECTROOXIDATION; OPTIMIZATION; Environmental Sciences & Ecology